FAKTOR PERSONAL AUDITOR INTERNAL DAN EFEKTIVITAS AUDIT INTERNAL - Gabriel Rosellini Wisnu Geraldin; Efraim Ferdinan Giri (LPPM STIE YKPN Yogyakarta, 2024)
This research aims to determine and analyze the influence of internal auditors' personal factors: experience, education and independence on the effectiveness of internal audits in manufacturing companies. The research instrument uses a questionnaire and variable measurement with a 4 (four) point Likert Scale on 100 respondents as a sample with the characteristics of internal auditors in manufacturing companies. Experience, Education and Independence will be tested for their influence on Internal Audit Effectiveness. The research results state that experience, education and independence have a significant influence on the effectiveness of internal audit. The results of this research imply that companies have a responsibility to position the internal audit function to be organizationally independent so that it can carry out effective audit tasks. Companies are required to plan and develop internal auditor resources by providing work experience in fields other than audit, and encourage professionalism by providing continuous learning opportunities and certification for internal auditors.